“PHONETIC STYLISTIC DEVICES” - ABDURAXMANOVA ZILOLA YOQUBJON QIZI; Begimkulova Xonzoda Suyun qizi (TADQIQOTLAR.UZ, 2023)
Annotation: This article delves into the realm of phonetic stylistic devices, uncovering the artful techniques writers use to enhance language through sound manipulation. The exploration includes well-known devices such as onomatopoeia, alliteration, assonance, consonance, and rhyme, each contributing to the auditory palette of language. The article also investigates the role of euphony and cacophony in crafting soundscapes that evoke specific emotions. By examining how these phonetic devices elevate the aesthetic and emotive qualities of language, the article highlights the intricate interplay between sound and expression, revealing language as a versatile and expressive medium.